(3OQQ GdMcGe aj TQM ZQQ GdCMcGes - (3edG NSQh, eMeO Hf aQGehR Hf Ydj, J (B885 (3g`s ((3eMeO Hf Ydjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CMce CMcGe GdTQY Gdbhje HeMce cJGHg hCYdG CYdGe GdOjf GdeSJbje HeYXe NWGHg hCSejJg HYO GdEJeGe OQQ GdMcGe aj TQM ZQQ GdCMcGes
(3BNQgG (B:s
(3MJi YKQJ Ydi eG UOQ Yf HYV GdCaGVd ef GdYKQGJ Ydi GdebJVi GdHTQjI hhbaJ Ydi eG hbY ef HYV GdCeGKd ef RdGJ djS faS GdEfSGf YfgG YQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 328s
(3eYLe GdeDdajf (B3 / 584s
(3cTa GdXfhf (B2 / 1199s
(3TPQGJ GdPgH (B7 / 342s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs